Warisan Sejarah dan Kewirausahaan : Sulam Bayangan dalam Penerapan P5 di SMAN 1 IV Nagari Bayang Utara Tahun 2024 - Sari, Indah Purnama; febriani, Eka Asih (Jurusan Sejarah FIS UNP, 2024)
The Pancasila Student Profile Strengthening Project (P5) at SMAN 1 IV Nagari Bayang Utara can be a means to introduce shadow embroidery as a historical and cultural heritage to students. P5 provides opportunities for students to not only gain theoretical knowledge, but also gain learning based on direct experience. This article also provides insight into the implementation of the psychological foundation of education in the entrepreneurship-based P5 program. The research method used in the process of writing this article is to use the historical research method consisting of a series of Heuristic, Verification, Interpretation, and finally Historiography processes. The results of this study indicate that the Pancasila Student Profile Strengthening Project (P5) by using the historical and cultural heritage of Shadow Embroidery to students has an impact on increasing students' social values ​​such as mutual cooperation, helping each other, and solidarity among students when making the shadow embroidery.